Carbon nanotube field-effect transistors and gaseous interactions - Peng, Ning (2010)
This thesis presents the major findings achieved in my Ph.D project on carbon nanotube (CNT) field-effect transistors (FETs) and gaseous interactions. It consists of four main parts: (1) AC dielectrophoretic (DEP) manipulation of CNTs; (2) studies of gaseous interaction in CNTFETs through selective Si3N4 passivation; (3) real-time detection of chemical gases using CNTFETs and (4) differentiating the sensing mechanisms in CNTFET-based NH3 detectors.